Clinical and functional results of patients after arthroscopic single row rotator cuff repair and arthroscopic acromioplasty - Dogar, Fatih; Topak, Duran; Temiz, Ahmet; Vatansever, Fatih; Kuscu, Burak; Bilal, Okkes (Annals of Medical Research, 2021)
Aim: The present study aims to evaluate clinical and functional results of arthroscopic single row rotator cuff repair and acromioplasty in patients with Rotator cuff tears (RCT).Materials and Methods: Sixty one patients whom were applied arthroscopic single row rotator cuff repair and arthroscopic acromioplasty between 2016 and 2019 were included in the present study. Patients’ rotator cuff tears (Patte classification) and acromion were classified based on X-ray and Magnetic Resonance Imaging (MRI) results. In addition, patients’ Constant Murley Scores, Shoulder Range of Motion (ROM) and visual analogue scale (VAS) scores were also analyzed prior to and following the surgical operation.Results: Forty one (67.2%) out of 61 patients in the present study were applied surgery on the right shoulders, while 20 of them (32.8%) were applied surgery on the left shoulders. Twenty one (34.4%) of patients were male, while 40 (65.6%) of them were female. Patients were divided into three groups as type 1 (n=10), type 2 (n=41), type 3 (n=10) based on their acromion classification and three stages as stage 1 (n= 15), stage 2 (n=36), and stage 3 (n=10) based on their rotator cuff tears. In addition, while their mean preoperative Constant-Murley and VAS scores were 29.8±0.79 and 9.14±0.11, respectively, it increased to 81.1±1.07 and decreased to 2.06±1.07 in the postoperative period, respectively. Finally, while patients’ preoperative mean abduction ROM was 60.73°±1.31°, it increased to 126.22°±2.27° in the postoperative period. Conclusion: Arthroscopic single row rotator cuff repair and arthroscopic acromioplasty in patients suffering from RCT contributes to significant relief of pain and remarkable increase in shoulder abduction ROM, thus offering an effective and reliable surgical treatment which allows the active use of extremities.